Endoplasmic reticulum stress involved in age-related nuclear cataract induced by sodium selenite - Yang Liu; Tong-tong Sha; Guang-li Sun; Shen-zhi Liang; Fang-fang Yu (Scientific Reports)
Abstract The proteomics were used to investigate the mechanism of sodium selenite causing age-related nuclear cataract in rats. Four pregnant Sprague–Dawley rats were selected, and the neonatal rats were randomly divided into three groups after natural delivery. The rats received subcutaneous injection of sodium selenite in LSe (10 µmol/kg·b.w) and HSe (20 µmol/kg·b.w) group, the rats received equal volume of normal saline in the control group. On postnatal day 21, these rats were sacrificed. Total proteins were extracted from lens tissues for proteomic analysis. Hematoxylin-eosin staining was used to determine the lens lesions. Immunohistochemistry staining and Western blot were used to verify the key proteins. In this study, the cataracts were observed in LSe and HSe group. In the control group, lens epithelial cells (LECs) were lined up with the same morphology, the lens fibers were arranged tightly and neatly. The base of LECs was closely connected with the lens fibers. In LSe and HSe group, the morphology of LECs were irregular, the lens fibers were disordered, vesicles and water cracks were observed within the fiberboard. Proteomic analysis identified 104 differentially expressed proteins (57 up-regulated and 47 down-regulated proteins), which were of great significance for the development of age-related nuclear cataract. KEGG pathway enrichment analysis revealed that protein processing in endoplasmic reticulum pathway was significantly enriched in the HSe group. According to the betweenness centrality, PPI network shown that Hspa5 was the hub protein, which was crucial for understanding and treating age-related nuclear cataract. Immunohistochemistry staining results showed the Hspa5, Manf and Calr were significantly up-regulated in LSe and HSe group. Western blot results showed the Hspa5 and Calr were significantly up-regulated in LSe and HSe group, which were consistent with our proteomic results. In conclusion, moderate sodium selenite induced endoplasmic reticulum stress, and led to age-related nuclear cataract of rats, in which Hspa5 played a key role.